Can citizen science analysis of camera trap data be used to study reproduction? Lessons from Snapshot Serengeti program. Issue 2 (3rd May 2021) - Thel, Lucie; Chamaillé‐Jammes, Simon; Keurinck, Léa; Catala, Maxime; Packer, Craig; Huebner, Sarah E.; Bonenfant, Christophe
Abstract : Ecologists increasingly rely on camera‐trap data to estimate biological parameters such as population abundance. Because of the huge amount of data camera trap can generate, the assistance of non‐scientists is often sought after, but an assessment of the data quality is necessary. We tested whether volunteers data from one of the largest citizen science projects – Snapshot Serengeti – could be used to study breeding phenology. We tested whether the presence of juveniles (less than one or 12 months old) of species of large herbivores in the Serengeti: topi, kongoni, Grant's gazelle, could be reliably detected by the 'naive' volunteers versus trained observers. We expected a positive correlation between the proportion of volunteers identifying juveniles and their effective presence within photographs, assessed by the trained observers. The agreement between the trained observers was good (Fleiss' κ > 0.61 for juveniles of less than one and 12 month(s) old), suggesting that morphological criteria can be used to determine age of juveniles. The relationship between the proportion of volunteers detecting juveniles less than a month old and their actual presence plateaued at 0.45 for Grant's gazelle, reached 0.70 for topi and 0.56 for kongoni. The same relationships were much stronger for juveniles younger than 12 months, reaching 1 for topi and kongoni. The absence of individuals < one month and the presence of juveniles < 12 months could be reliably assumed, respectively, when no volunteer and when all volunteers reported a presence of a young. In contrast, the presence of very young individuals and the absence of juveniles appeared more difficult to ascertain from volunteers' classification, given how the classification task was presented to them. Volunteers' classification allows a moderately accurate but quick sorting of photograph with/without juveniles. We discuss the limitations of using citizen science camera‐traps data to study breeding phenology, and the options to improve the detection of juveniles.